2016
DOI: 10.1177/1708538116673770
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of the platelet-to-lymphocyte ratio with the severity of stenosis and stroke in patients with carotid arterial disease

Abstract: Objectives Platelet-to-lymphocyte ratio is a novel biomarker, recently shown to be correlated with atherosclerotic inflammation. This study investigated the role of platelet-to-lymphocyte ratio in patients with carotid artery stenosis and stroke. Methods Patients, who underwent carotid angiography with Multiple Detector Computed Tomography Angiography at our hospital, were retrospectively screened. Patients enrolled were divided into three groups based on the platelet-to-lymphocyte ratio. Patients with a plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…In the study of cerebrovascular diseases, an increased PLR was considered a predictor of stroke (35). Studies have suggested that low PLR levels could be a highly negative predictive value to rule out stroke events for patients with carotid artery stenosis (CAS) (36). In another study, high PLR values could indirectly estimate the infarcted size of stoke patients and the poor recanalization rate after thrombectomy therapy (13).…”
Section: Discussionmentioning
confidence: 99%
“…In the study of cerebrovascular diseases, an increased PLR was considered a predictor of stroke (35). Studies have suggested that low PLR levels could be a highly negative predictive value to rule out stroke events for patients with carotid artery stenosis (CAS) (36). In another study, high PLR values could indirectly estimate the infarcted size of stoke patients and the poor recanalization rate after thrombectomy therapy (13).…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, the fasting blood glucose, lipid profile, complete blood count and total testosterone level that are requested by clinicians are among these tests (Burnett, ). Studies conducted on NLR and PLR values, which show the relation between systemic inflammation and many diseases in ED and aetiology, are increasing in the present literature (Furuncuoğlu et al, ; İdil Soylu et al, ; Meng et al, ; Tulgar et al, ; Varım et al, ; Xu et al, ). When we selected our study group, we included not only the pre‐treatment values, but also those who were asked for a CBC for any reason to determine the changes in the 1st month after PDE5i treatment, which is different from previous studies.…”
Section: Discussionmentioning
confidence: 97%
“…Idil Soylu et al conducted a study and showed that the PLR rate was positively correlated with carotid arterial stenosis ( r = 0.250, p = 0.002) (İdil Soylu et al, ). Mertoğlu et al showed that the mean NLR values were statistically higher in patients with pre‐diabetes (1.60 ± 0.85) and those who were diagnosed newly (1.58 ± 0.78) and in patients with diabetes (2.07 ± 0.95) when compared to the normal group (1.37 ± 0.69); and the mean PLR value was higher in the diabetic group (122.45 ± 37.43) (Mertoglu & Gunay, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Platelet/lymphocyte ratio (PLR) is considered to be a recent biomarker which is not only related with inflammation but also associated with the atherosclerotic process which may lead to plaque rupture. 7 In some studies, a positive clinical correlation was found between PLR count and the incidence of coronary artery disease, 8 the degree of carotid artery stenosis, 9,10 the incidence of peripheral artery disease, 11,12 and the incidence of aortic valve stenosis. 13 However, data on the association between PLR and carotid artery stenosis in patients undergoing carotid endarterectomy (CEA) are lacking.…”
Section: Introductionmentioning
confidence: 99%